«E los que las tienen escriptas las ronpan, tiren, e chançellen»: censorship systems and legislative background to the Spanish Indexes of Forbidden Books - Jiménez Pelagio, Nerea (Revista General de Información y Documentación, 2025)
The Indexes of Forbidden Books were a tremendously effective tool of bibliographic control to regulate the content and form of printed works from the second half of the 16th century onwards. However, these indexes, which have been extensively studied from various disciplines, not only draw on, but also adapt the legislation enacted in the preceding centuries. Despite this, little is known about the systems of regulation and control of the libraries of the previous centuries in the territories of the Hispanic monarchy. The legislation regulating the production, dissemination and possession of Spanish religious books, both manuscript and printed, issued by the ecclesiastical and civil authorities in the centuries prior to the 16th century, is compiled and studied in order to assess the extent to which it influenced the application of prohibitions and the exercise of censorship in Spanish religious books prior to the introduction of the Index of Prohibited Books.